2023
DOI: 10.3389/fvets.2023.1225446
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling at the livestock-wildlife interface: scoping review of drivers of disease transmission between species

Brandon H. Hayes,
Timothée Vergne,
Mathieu Andraud
et al.

Abstract: Modeling of infectious diseases at the livestock-wildlife interface is a unique subset of mathematical modeling with many innate challenges. To ascertain the characteristics of the models used in these scenarios, a scoping review of the scientific literature was conducted. Fifty-six studies qualified for inclusion. Only 14 diseases at this interface have benefited from the utility of mathematical modeling, despite a far greater number of shared diseases. The most represented species combinations were cattle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…A recent review identified the milieu of approaches to estimating parameters and assessing control strategies of multi-host epidemics, though only five of the 56 examined approaches used a similar pointlocation-over-habitat-raster framework (46). Noteworthy, this approach was recently employed by a team in the ASF Modelling Challenge (47,48).…”
Section: Model Formulationmentioning
confidence: 99%
“…A recent review identified the milieu of approaches to estimating parameters and assessing control strategies of multi-host epidemics, though only five of the 56 examined approaches used a similar pointlocation-over-habitat-raster framework (46). Noteworthy, this approach was recently employed by a team in the ASF Modelling Challenge (47,48).…”
Section: Model Formulationmentioning
confidence: 99%